STRATEGI PERLAWANAN BERKEDOK KOLABORASI Sebuah Tinjauan Antropologi Kasus Penguasaan Hutan - Prudensius Maring (Partner, 2010)
Strategy of Resistance Under the Guise Of Collaboration: An Anthropological View on Case of Forest Tenure. The implementation of the projects on the state forest area provides collaboration between the local community and the government. Although, the first step and during the process, the local community effort to control the forest area through tactic to select the seed of the tree, reveal the location of the project, and get the certificate of the forest land. The situation show a collaboration contained strategy of resistance from the community to respond the authority of the government. The analysis inspire qualitative research approach and theory of resistance. Theoretically, the result of the analysis show a dynamic pattern of community’s resistance. The result change the old views of the community’s resistance which has been defined anonimously, hiddenly, quietly, and secretly. The phenomenon construct new discussion about dynamic relation of power. Practically, the result of the analysis underline the urgency of the forest development approach which respect and recognize the local community rights.Keywords: Collaboration, strategy of resistance, relation of power, forest tenure, qualitative research approach